Linear sweep voltammetry at the tubular electrode: Theory of EC2 mechanisms - Streeter, I; Thompson, M; Compton, R (2006)
Concentration profiles are obtained via numerical solution for the species involved in an EC2 mechanism in a tubular flow cell. Voltammetric waves are simulated and the variation of the half-wave potential as a function of the kinetic parameters is explored. Criteria are presented for the analysis of expected current/voltage curves.